Relationship between Corvis ST tonometry parameters and mean blur rate in the optic nerve head tissue area in healthy eyes - Yuta Nakaniida; Fumiko Higashikawa; Kana Tokumo; Shunsuke Nakakura; Ryo Asaoka; Yoshiaki Kiuchi; Hirokazu Sakaguchi (PLoS ONE, 2026)
This study investigated the relationship between Corvis ST tonometry parameters and mean blur rate in the optic nerve head tissue area (MBR-T) in healthy eyes. Corneal biomechanical properties and MBR-T were measured in 100 eyes from 56 healthy participants in Japan using Corvis ST tonometry and laser speckle flowgraphy, respectively. Axial length, central corneal thickness, and intraocular pressure were also recorded. Linear mixed-effects models were applied to evaluate the associations between corneal biomechanical properties and MBR-T. Model selection was performed using the second-order bias-corrected Akaike Information Criterion (AICc). The optimal predictive model for MBR-T was as follows: MBR-T = 21.1607 (intercept) – 1.6317 × Sex (Male) – 4.8626 × A2 deformation amplitude – 5.7932 × HC deformation amplitude (AICc = 409.9). In healthy eyes, greater corneal deformability was associated with lower MBR-T.